Heterogeneous Bulk Polymerization of Styrene in the Presence of Polybutadiene. Calculation of the Macromolecular Structure - Casis, Natalia (2006)
A mathematical model is presented that simulates the polymerization of styrene in the presence of polybutadiene (PB) for producing high-impact polystyrene (HIPS) via the heterogeneous bulk process. The model follows the polymerization in two phases; and calculates in each phase the main reaction variables and the molecular structure of the three polymeric components: free polystyrene (PS), unreacted PB, and graft copolymer. Two polymerizations (at 90 and 120°C) were carried out and simulated. The model was validated with measurements of the monomer conversion, the grafting efficiencies, and the average molecular weights.